An mRNA-based vaccine candidate against SARS-CoV-2 elicits stable immuno-response with single dose. Issue 28 (23rd June 2021) - Nag, Kakon; Chandra Baray, Juwel; Rahman Khan, Maksudur; Mahmud, Asif; Islam, Jikrul; Myti, Sanat; Ali, Rostum; Haq Sarker, Enamul; Kumar, Samir; Hossain Chowdhury, Mobarak; Roy, Rony; Islam, Faqrul; et al.
Abstract: D614G genotype of SARS-CoV-2 virus is highly infectious and responsible for almost all infection for 2nd wave. However, there are currently no reports with D614G as vaccine candidate. Here we report the development of an mRNA-LNP vaccine with D614G variant and characterization in animal model. We have used special mRNA-architecture and formulation that provides suitable response of the product. The surface plasmon resonance (SPR) data with spike protein (S) revealed that immunization generated specific antibody pools against the whole extracellular domain (RBD and S2) of the spike protein. The anti-sera and purified IgGs from immunized mice neutralized SARS-CoV-2-pseudoviruses in ACE2-expressing HEK293 cells in a dose dependent manner. Importantly, single-dose immunization protected mice-lungs from homotypic-pseudovirus entry and cytopathy. The immunologic responses have been implicated by a balanced and stable population of CD4+ cells with a Th1 bias. The data suggested great promise for immediate translation of the technology to the clinic.